Mediators of physical activity behaviour change among adult non-clinical populations: a review update - Rhodes, Ryan E (BioMed Central, 2010)
BACKGROUND: An understanding of the determinants of physical activity through mediators of behaviour change is important in order to evaluate the efficacy of interventions. Prior reviews on this topic noted that few studies employed mediator analyses in experimental physical activity trials; the purpose of this review is to update these prior reviews in order to evaluate the state of our present understanding of interventions that include proposed mediators of behaviour change. METHODS: Literature was identified through electronic database (e.g., MEDLINE, psychINFO) searching. Studies were eligible if they described a published experimental or quasi-experimental trial examining the effect of an intervention on physical activity behaviour and mediator change in non-clinical adult populations. Quality of included studies was assessed and the analyses examined the symmetry between mediators and behaviour change. RESULTS: Twenty seven unique trials passed the eligibility criteria and 22 were included in the analysis with scores of moderate or higher quality. Half of the studies reviewed failed to show an intervention effect on PA. The remaining studies showed evidence that the intervention affected changes in the proposed mediators, but tests of mediated effect were performed in only six of these 11 cases and demonstrated mixed outcomes. Differences by theory were not discernable at this time, but self-regulation constructs had the most evidence for mediation. CONCLUSION: Published literature employing mediators of change analyses in experimental designs is still relatively elusive since the time of prior reviews; however, the general null findings of changes in mediating constructs from these interventions are a more timely concern. Changes in self-regulation constructs may have the most effect on changes in PA while self-efficacy and outcome expectation type constructs have negligible but limited findings. Innovation and increased fidelity of interventions is needed and should be a priority for future research.